EXPLORING FOREIGN APPROACHES TO FOSTERING SUSTAINABLE ECONOMIC GROWTH - Komilov M. I.; Toshtemirov M. O.; Kurpayanidi K.I. (Scholars Digest Publishing, 2024)
This article offers a comprehensive examination of international strategies and methodologies employed to drive sustainable economic growth through the integration of green economy principles. The research meticulously investigates the utilization of renewable energy sources within the specific context of Uzbekistan, scrutinizing current usage patterns, discerning developmental trends, and pinpointing inherent challenges. By synthesizing global best practices with local realities, the study identifies crucial structural adjustments necessary for fostering sustainable economic development within the national economy of Uzbekistan. Through a detailed analysis of foreign experiences and domestic imperatives, this article not only sheds light on the complexities of sustainable economic growth but also formulates actionable proposals and strategic recommendations tailored to the unique socio-economic landscape of Uzbekistan. These insights are poised to inform policy decisions and drive meaningful progress towards a more sustainable and resilient economic future for Uzbekistan.
Keywords: Sustainable economic growth, Green economy, Renewable energy sources of Uzbekistan, Development trends, Structural changes, Foreign approaches, Policy recommendations, Economic resilience, Sustainability.